A interpretação dos contratos complexos: uma visão dos contratos coligados - Gomes, Susete (2017)
In business context, freedom (inserted in the private autonomy context) lays foundations to the so-called complex contracts, which may be named as so due to aspects of different nature (subjective, normative, volitional, and objective). They are atypical, besides tending to show gaps and being of duration and relational. Complex contracts attract other contracts that become related to them, forming a complex contractual system. It is to this matter that this study converges by aiming to address the interpretation of complex contracts, including an overview of related contracts. The research underlying this thesis is relevant because its theme was given almost none doctrine treatment; moreover, there is an increasing demand for such contracts in the business market. Achieving such an aim required synchronizing the demand for complex contracts with contemporary society and its complexity, which imposes the need to reduce complexities by means of selection (choices). For that, the language works as a mediator of distinct complexities arising from the legal, economic and political systems. The interpretation of complex contracts must be drawn from the concrete situation: all various elements making it up are allocated according to its economic and practical function, which is revealed by its specific cause; the elements are filtered by the vector of the circumstances of the case so that the filtered ones are weighed against the legal system by means of general clauses of objective good faith, contractual balance and social function of contracts. Therefore, in a process called “meta-contractuality”, rules to interpret the complex contractual system will derive from the complex contract itself to be used in the same contractual system in case of conflicts to solve